Improved dextran preparation of human leucocytes for chemiluminescence analysis of the oxidative burst of polymorphonuclear cells - Cíz, M; Lojek, A (Clinical and laboratory haematology, 1997)
An improved method for the preparation of leucocyte-rich plasma from human blood samples for chemiluminescence (CL) analysis is described. Heparinized blood is layered over 4% dextran in a ratio of 1:1 (v/v). The leucocyte-rich plasma is obtained after a 1 h sedimentation of the erythrocytes. When compared with the plasma obtained by the usual method of mixing blood with dextran, the residual red cell count was reduced. On the other hand, the index of phagocytosis (peak values of activated phagocytosis/spontaneous phagocytosis) was increased. This is caused by increased spontaneous CL activity after mixing blood with dextran, which can activate leucocytes. Such activation was observed both in plasma samples and in whole blood samples when measured immediately after dextran addition or after 1 h incubation with dextran.
Keywords: respirační vzplanutí; Dextrans; luminiscenční měření; Luminol; fagocytóza; Luminescent Measurements; Humans; dextrany; Respiratory Burst; lidé; Leukocytes; Phagocytosis; luminol; leukocyty